Method of temperature control and duration of aging of beryllium bronze products - A. V. Tolstoy (Литьë и металлургия, 2022)
A non‑destructive X‑ray diffraction control method has been developed to determine the temperature and duration of aging of beryllium bronze products. The control method is based on the dependences of the magnitude of the interplane distance of the released phase and the broadening of the diffraction line of the solid solution on the aging regime. To implement the developed control method, the dependences of the broadening of the diffraction line of the solid solution and the magnitude of the interplane reflection distance 100 of the released phase on the duration of aging at different temperatures are preliminarily determined. According to these dependencies, a nomogram is built, which is later used to control aging regimes. It is established that the reliability of determining the heat treatment mode depends on the instrumental factor associated with the difference in the geometric shape of the membranes of the elements, as well as on the amount of texture that occurs during plastic deformation of the material at the technological stages of product manufacturing. A method is proposed to minimize the influence of these factors on the accuracy of measurements.